2003
DOI: 10.3727/000000003108747109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of VEGF on the Viability of Encapsulated Pancreatic Rat Islets after Transplantation in Diabetic Mice

Abstract: After pancreatic islet transplantation, insufficient blood supply is responsible for the loss of islet viability. The aim of our study was: 1) to determine the influence of vascular endothelial growth factor (VEGF) on the survival of encapsulated rat islets transplanted into healthy and diabetic mice and 2) to evaluate the metabolic efficiency of the VEGF-supplemented grafts. Twenty-four hours after culture, 50 rat islets immobilized into collagen in the presence of VEGF (100 ng/ml) and encapsulated (AN69 memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 31 publications
4
62
0
Order By: Relevance
“…48 Likewise, normalization of glycemia occurred when fibrin-encapsulated VEGF-treated rat islets were transplanted into diabetic mice. 49 Results from these studies in combination with our own confirm that blood vessel formation is important for the maintenance of islet graft function and survival.…”
Section: Discussionsupporting
confidence: 65%
“…48 Likewise, normalization of glycemia occurred when fibrin-encapsulated VEGF-treated rat islets were transplanted into diabetic mice. 49 Results from these studies in combination with our own confirm that blood vessel formation is important for the maintenance of islet graft function and survival.…”
Section: Discussionsupporting
confidence: 65%
“…Using a different approach by which murine islets were immobilized with collagen in the presence of VEGF protein and encapsulated before transplantation into the peritoneal cavity, Sigrist et al (37) showed that local release of VEGF within the grafts significantly increased the viability of transplanted islets, resulting in extended physiological control of glycemia in STZ-induced diabetic mice. Although therapeutic angiogenesis has been used for treating coronary and peripheral artery diseases by facilitating new vessel formation using plasmid or adenoviral vector-mediated VEGF gene delivery in a number of clinical trials (38 -44), our present results together with others suggest that a similar strategy should be explored to allow local production/release of angiogenic molecules in islet grafts to accelerate islet revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of rapid revascularization is expected to improve the viability and functioning of transplanted islets. This may be achieved by ex vivo VEGF gene delivery to islets (Narang et al, 2004) or by coencapsulating VEGF protein with islets during microencapsulation (Sigrist et al, 2003a). These approaches are discussed in section V.…”
Section: B Inadequate Revascularization Of Transplanted Isletsmentioning
confidence: 99%